"We know who is a cheat and who is not. But what can you do?": Athletes` perspectives on classification in visually impaired sport - Powis, B.; Macbeth, J. L. (International Review for the Sociology of Sport, 2020)
Classification in disability sport is an issue mired in controversy. Much of the recent public scrutiny of classification systems and processes has been directed towards to the Paralympics, the showcase global disability sport event. But this is not just a Paralympic issue; the controversy of classification pervades disability sport at all levels. Using an embodied approach to disability sport, this article reveals how classification is experienced and regarded by visually impaired football and cricket players. We present findings from two qualitative research projects: one with the England Cricket Team between 2014 and 2016 and one with both grassroots and elite footballers in 2017. Our research reveals significant commonalities in the players` experiences of classification, including: a lack of faith in a classification system which does not adequately capture the diversity of visual impairment; visual impairment classes as social identifiers; rumour and gossip about intentional misrepresentation. The experiences of these visually impaired athletes add an important perspective and original contribution to the current literature on classification which, until now, has focused entirely on the Paralympic context.